IMPACT OF SAVING HABITS ON FINANCIAL BEHAVIOUR OF UNIVERSITY STUDENTS - NAKALEMA JANE PATRICIA (UGANDA CHRISTIAN UNIVERSITY, 2025)
This study aimed to explore how students’ saving habits influence their financial behaviors, focusing on BBA 3:2 Students 2022-2025. There were three specific objectives: to examine the relationship between saving habits and financial behavior among university students, to identify the factors that influence saving habits among students at Uganda Christian University, and to identify the problems affecting saving habits and financial behavior among university students, along with suggesting potential solutions. Through a cross-sectional research design approach, the researcher was able to understand the relationship between saving habits and financial behaviors among university students. The researcher received a total of 53 responses out of the 60 students expected to complete the survey. Therefore, the response rate was 88.3% (53/60). The high response rate indicated the students’ willingness to inform about their saving habits and financial behaviors. The researcher reports the findings using descriptive statistics, including mean, median, frequencies, and proportions of the different included variables. The mean (SD) age of the students was 25.5 (SD 3.34), with a composition of female (58.5%) and male (41.5%), specializing in finance (41.5%) and accounting (37.7%), management (15.1%), and marketing (5.7%). Approximately 75.5% reported having some money saved, with about 24.5% of the students having no money saved anywhere. Overall student’s responses indicated that almost all students (96.2%) either agreed or strongly agreed that having good saving habits helps them to manage their finances better, indicated by a high mean score of 4.5, with the majority of them agreeing (45.3%) or strongly agreeing (30.2%) that they regularly save money, which improves their overall financial behaviour. After conducting a bivariate correlation analysis test to check for the relationship between saving habits and financial behaviors, the correlation coefficient (R-Value) of 0.285 indicated that there was a significant weak positive relationship between saving habits and financial behaviors. Some problems that affected students’ saving habits and financial behaviors included unexpected expenses, difficulties encountered by students to save, lack of financial education or training for students, digital saving tools or campus programmes, issues with peer influence, students prioritizing immediate wants over long-term saving, and lack of income-generating opportunities for students. Students suggested organizing savings awareness campaigns on campus (75.4%) and making saving easier through digital tools or on campus (54.7%) to improve their saving habits and encourage more frequent saving. The findings of this research indicate a statistically significant correlation between saving habits, such as setting savings goals and budgeting, and financial behaviours. Financial literacy within the university among students is crucial to empower students to understand why they should save, set saving goals, and learn how to track their budget and expenses.
UNDERGRADUATE